Peningkatan Pemahaman Etika Berumah Tangga melalui Kajian Islami pada Masyarakat Desa Balongwono, Kecamatan Trowulan - Lailatus Sa'adah; Ahmad Taqiyuddin; Amsi Alkartadi; Mufarrihatul Hasan; Aisyah Zulfa Mazadha; Usfatun Khusniyah; Atiqoh Nur Azizah (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
In Balongwono Village, emerging household problems are inextricably linked to the influence of modernization, economic activity, and the rampant, unwise use of social media. Although the Balongwono community is known to be quite religious, ethical household values have not yet been fully internalized in daily life. Given this situation, Islamic studies on household ethics are essential in Balongwono Village. The potential for success of this program is quite high, given the community's high enthusiasm for attending religious studies, supported by the presence of respected religious figures, adequate worship facilities, and a strong tradition of mutual cooperation. Implementation methods include thematic studies with resource persons, interactive discussions, and the use of learning media in the form of easy-to-understand pocket books. Program evaluation is carried out through pretests and posttests. The results showed a significant increase from an average pretest score of 73.11 to 94.44 in the posttest, with all participants classified as capable. This success demonstrates not only the effectiveness of the method but also the community's enthusiasm for participating. This program has made a positive contribution by increasing understanding of Islamic household ethics and is expected to continue through regular village religious study activities.